Mapping growth and trajectory in the field of extracellular vesicles: A scientometric analysis - Liam Hourigan; William Phillips; Amirmohammad Nasiri Kenari; Krishna Chaitanya Pavani; Chaomei Chen; An Hendrix; Lesley Cheng; Andrew F. Hill (Extracellular Vesicle)
Extracellular vesicles (EVs) are a diverse population of membrane bound particles released by cells. They play roles in a variety of diseases and biological functions, piquing the interest of researchers and industry alike. The field is often described as undergoing ‘explosive growth’, however this growth has not been characterized in depth. Scientometrics is a quantitative approach for analyzing scientific works, allowing for a broadly focused review of the EV field. Drawing on 52210 publications from the Web of Science, this review charts the field's using the programs CiteSpace and Bibliometrix. These analyses are further enriched with data from the Dimensions database along with data from EV-TRACK, an EV-specific data source. We thoroughly describe the field's various subdomains, identifying their different lines of inquiry, their variable use of nomenclature and their progression along the translational pipeline. Cancer features prominently alongside other diseases and conditions, with the majority of research having a basic aetiological focus. These subdomains are compared against a global map of science, revealing a stable and substantial EV research community revolving around the International Society for Extracellular Vesicles ISEV and the ‘MISEV paradigm’. A shared framework of knowledge and communication, grounded in the field's history and guiding its future.